Spatial modeling of the use probability for Pig-nosed turtles (Carettochelys insculpta) in South Papua, Indonesia - PURNAMA GRAHA; MIRZA D. KUSRINI; SYARTINILIA SYARTINILIA; RICHARD GATOT NUGROHO TRIANTORO (Society for Indonesian Biodiversity, 2024)
Abstract. Graha P, Kusrini MD, Wijaya S, Triantoro RGN. 2024. Spatial modeling of the use probability for Pig-nosed turtles (Carettochelys insculpta) in South Papua, Indonesia. Biodiversitas 25: 3246-3253. The uncontrolled use of natural resources can threaten species' survival and negatively impact ecosystems, potentially affecting the economy and its service to humans. One species that requires attention is the pig-nosed turtle (Carettochelys insculpta Ramsay, 1886), the sole surviving member of the Carettochelyidae family and is only found in rivers of southern New Guinea and the northern regions of Australia. Pig-nosed turtles have been harvested intensively in Papua for their eggs and are considered vulnerable based on the International Union for Conservation of Nature red list assessment. Developing a spatial distribution model to determine the probability of use of C. insculpta priority areas is crucial to safeguard the essential areas necessary for its life cycle. This research utilized the Ecological Niche Modeling at The Metaland EcologyLab to assess use probability and identify potential conservation risks. Results of the probability of use model analysis in South Papua Province revealed that the region with the highest use probability of C. insculpta is Boven Digoel District, accounting for a significant land area of 496,019.61 hectares. In comparison, moderate use was noted in Asmat District, encompassing 921,830.76 hectares, whereas low use was recorded in the same regency, covering 695,466.10 hectares. The use probability was influenced by multiple factors, with the most significant contributions stemming from the occurrence of water (41%), distance from the settlement (21%), distance from road (14%), land cover (13%), river density (6%), and slope (5%).